Analysis of Consumer Behavior in the Usage of OVO in the Special Region of Yogyakarta Province: Integration of Theory Acceptance Model and Extended Theory of Planned Behavior - Rifki, Akbar Faiz; Sugandini, Dyah; Sutiono, Heru Tri (UPN Veteran Yogyakarta, 2024)
This research aims to investigate consumer behavior in using OVO in DIY Province through the integration of the Theory Acceptance Model (TAM) and the Extended Theory of Planned Behavior (TPB). The object of this research was carried out in DIY Province with a total sample of 203 respondents who met the criteria. Research data was obtained through distributing questionnaires online which was then processed via Smart PLS to determine the influence between the variables tested. The research results found that perceived benefits and perceived ease of use influence attitudes towards using the OVO application. Besides that, attitudes, subjective norms and perceived behavioral control have a significant effect on behavioral intentions in using the OVO application. Research shows that perceived usefulness (β=0.405) has a stronger influence on attitudes compared to perceived ease of use (β=0.151). Meanwhile, perceived behavioral control (β=0.532) has a higher influence on behavioral intentions compared to attitudes (β=0.241) and subjective norms (β=0.130).